Determinants of Business Ethics, Organizational Culture, Employee Engagement, and Job Performance of Flight Attendant - Jitklongsub, Jitti; Suveatwatanakul, Chokechai (Dusit Thani College Journal, 2020)
This study illustrates determinants of factors that are relevant to Business Ethics Organizational Culture Employee Engagement and Job Performance of Flight Attendant. According to qualitative research method, the review of textbooks, documents, and research studies was applied. Four of relevant factors are related to Business Ethics. Three of relevant factors are related to Organizational Culture. Five of relevant factors are related to Employee Engagement, and factors of success for Job Performance have 4 relevant factors. The finding of this paper will be applied for the future research which analyze the factors influencing aviation industry indicators of success concerning Job Performance of Flight Attendant in terms of Business Ethics, Organizational Culture, and Employee Engagement.